2022
DOI: 10.1088/1742-6596/2192/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of particles of the dispersed system based on low-concentrated aqueous solutions of L-cysteine and silver acetate

Abstract: The authors of this work conducting a study of the precursor of reference materials of the zeta potential of particles in dispersed systems. The precursor is based on supramolecular solution of L-cysteine and silver acetate (CSSac). Particles and aggregates of CSSac were studied by dynamic light scattering (DLS), phase analysis of scattered radiation (PALS), inductively coupled plasma mass spectrometry (ICP-MS) and high-resolution transmission electron microscopy (HR-TEM). It was established that the diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…On the other hand, the particle size closely correlates with ζ potential, with nanometric sizes facilitating optimal dispersion of hydrocolloids and thereby promoting stability [ 21 , 22 ]. It has been observed that the particle size of SDH in solution decreases considerably with the progression of storage time ( Figure 8 c), initially ranging between 650 to 900 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the particle size closely correlates with ζ potential, with nanometric sizes facilitating optimal dispersion of hydrocolloids and thereby promoting stability [ 21 , 22 ]. It has been observed that the particle size of SDH in solution decreases considerably with the progression of storage time ( Figure 8 c), initially ranging between 650 to 900 nm.…”
Section: Resultsmentioning
confidence: 99%
“…This aspect becomes particularly significant in preventing the undesired sedimentation of suspended solids, a concern in various liquid products such as nectars, juices, and dairy-derived concentrates, and especially in the context of suspended drugs. Conversely, in applications where agglomeration is desired, such as certain processes [ 18 , 19 , 20 , 21 , 22 ], sedimentation becomes a favorable outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Методами электронной микроскопии и динамического рассеяния света установлено, что частицы в супрамолекулярных системах представлены в виде агрегатов размерами до 1 мкм из связанных между собой частиц [6][7][8]. В исследованиях системы на основе ацетата серебра с L-цистеином с применением метода масс-спектрометрии с индуктивно-связанной плазмой установлено, что наименьшее значение частиц в системах составляет 5-7 нм [9]. Методами просвечивающей электронной микроскопии и элементного анализа установлено, что этими частицами являются наночастицы серебра, которые связаны между собой в агрегаты размерами до 50 нм [9].…”
unclassified
“…В исследованиях системы на основе ацетата серебра с L-цистеином с применением метода масс-спектрометрии с индуктивно-связанной плазмой установлено, что наименьшее значение частиц в системах составляет 5-7 нм [9]. Методами просвечивающей электронной микроскопии и элементного анализа установлено, что этими частицами являются наночастицы серебра, которые связаны между собой в агрегаты размерами до 50 нм [9]. Связывание между наночастицами происходит посредством комплексов вида Ag + /Цис, связанных между собой в виде линейных цепочек вида (-Ag-S(Cys)-Ag-S(Cys)-)n и образующих трехмерную структуру.…”
unclassified